Home networks a standards perspective. - Rose, B. (IEEE Communications magazine)
An overview of home networks, as defined by the Home Networking and IT (HNIT) Division of the Consumer Electronics Association (CEA), is presented in this paper. HNIT's membership includes consumer electronics executives, marketing and market research professionals, engineers, and standards developers, which provide a broad perspective on this subject. The article first introduces the rational behind the definition. From that baseline, it moves on to review some of the most critical issues home networks must address so as to meet the expectations of content and service providers-and ultimately those of the consumer. With that foundation, the article provides an overview of each of the major home networking protocols and standards, as well as their respective strengths and weaknesses. Also included is a discussion of the interrelationships between the major standards and industry specifications: in other words, how they will work together to create a seamless home network environment